A Classroom Action Research: Using Quick Write Strategy to Improve Grade IX NPM Thailand Students’ Self-confidence in Writing - Suksawai, Pawinee; Zaki, Leil Badrah; Prasodjo, Pandu (Institut Agama Islam Negeri Palopo, 2025)
The aims of this research are to implement a suitable teaching strategy for overcoming the students’ unconfident in writing by using quickwrite strategy and also tried to find how do the students perceive the implementation. This research employs a qualitative method which is action research. Purposive sampling was used in this reserch. The research participants were taken from students in the ninth-grade students, class five at Nongchok Phitthaya Nussorn Mattayom School, with 37 students. The instruments of the study are classroom action research with one group pretest-posttest design by using a paragraph writing test and a survey questionnaire which is the students’ satisfaction survey. The writer analyzed the data using SPSS 26 to see the total score and the range of written words. Participants' survey responses will be examined for common and recurring themes in their responses. The study's findings indicate that the Quickwrite strategy was effective in improving students' writing self-confidence because there was a development score between the pre-test, treatment 1, and post-test, which can be supported by the mean score of the written words by students in each test. The students had a good attitude and were more engaged in studying English writing with the quickwrite strategy.